Efektivitas Program Operasi Pasar Penutupan Satu Abad NU di Pondok Pesantren Lirboyo Kediri - Risma Ardana Reswari; Singgih Manggalou (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The market operation program is an activity to sell groceries at a lower price than the lowest selling price outside. This activity was carried out officially by the East Java Provincial Government and in collaboration with PT. Puspa Agro as a subsidiary of PT. Jatim Grha Utama which is one of the East Java Regional Owned Enterprises. Market operations carried out by PT. Puspa Agro cooperates with the Provincial Government of East Java. The Market Operation Program was organized by Nahdlatul Ulama in commemoration of the closing of the 1st Century of NU. The program was organized with the aim of providing sales with a lower difference than the prices sold outside. The method used by the author in this research is descriptive research with a qualitative approach. This study uses several variables to measure program effectiveness, namely program socialization, program objectives, and program monitoring. According to the research that has been done, it can be seen that the effectiveness of the re-registration program has not been fully fulfilled. Due to the implementation there are problems such as the location which is within the Pondok Pesantren area and the lack of spread of program socialization.